Peninjauan Partisipasi Politik Bagi Perempuan Pada Pemilu 2019 di Kecamatan Meureubo - Rahma Hidayati; Fiandy Mauliansyah (Jurnal Pengabdian Masyarakat: Darma Bakti Teuku Umar, 2019)
This article wants to see how the participation of women in Meureubo sub-district in welcoming the democratic party during the election of legislative candidates in April 2019. As is known, the involvement of women in politics is still very low. The method used is the Lecture method and then discusses with women representatives from several villages in the Meureubo sub-district. The results show that some of them chose women legislative candidates due to various reasons, namely only women who understood about women so that there was a need for women's representation in parliament, women rarely tripped over corruption cases, women were not equal to men. But for those who do not vote for women legislative candidates due to reasons, namely women are not fit to be leaders, the election of women candidates is only for fulfillment of the quota so that party choices are less than optimal, women are less capable of politics. However, in the end they only hoped that the representation of women or men in the legislature could help empower other women, especially from Meurebo sub-district.